2018
DOI: 10.1108/bfj-04-2017-0208
|View full text |Cite
|
Sign up to set email alerts
|

The secrets of the longevity of informal retail markets in Croatia

Abstract: Purpose Despite modern retail formats, for many cultures, informal markets (street markets, farmers’ markets, or wet markets in Asia), fleas, and bazaars still remain an important part of life. The purpose of this paper is to provide further insight into the characteristics of informal retailers, and to explain their growth and longevity in markets. Design/methodology/approach In order to explore what attracts customers to informal retail markets, a survey conducted on the sample of Croatian consumers was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
1
11
0
1
Order By: Relevance
“…This study reinforced the position held by many researchers that the informal vendors are a critical part of urban life (Cross and Morales, 2007; Ikioda, 2013; Renko and Petljak, 2018; Roy, 2009). Results of the study on vendors indicated that many of them do not have fixed spots to vend in, and they get their vending spots using different means, whether through social networks or agreements.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This study reinforced the position held by many researchers that the informal vendors are a critical part of urban life (Cross and Morales, 2007; Ikioda, 2013; Renko and Petljak, 2018; Roy, 2009). Results of the study on vendors indicated that many of them do not have fixed spots to vend in, and they get their vending spots using different means, whether through social networks or agreements.…”
Section: Discussionsupporting
confidence: 84%
“…These markets have, on the one hand, been thought of as temporary, and that they would be replaced by larger, formal institutions as a place progressed economically (Bougoure and Lee, 2009; Chen, 2012; Sehib, et al , 2013). On the other hand, researchers on urban informal markets have maintained that these organic, spontaneous and unregulated activities are a critical part of urban life (Cross and Morales, 2007; Greenspan, 2018; Ikioda, 2013; Renko and Petljak, 2018; Roy, 2005, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second part was employed to evaluate consumer perceptions of different market aspects. Its maximum score was 210 points for assessing some of the aspects linked with food safety, such as the products sold (50), food handlers' training (40) and market hygiene (40), as well as others unrelated to food safety, such as professionalism (40) and price (30), using several questions about each item. The intention of this differentiation was to know which aspects consumers valued the most and whether they were related to food safety.…”
Section: Surveymentioning
confidence: 99%
“…Pasar ini tumbuh secara unorganized tanpa melalui perencanaan dan perancangan. Operasional dan tata kelola juga berjalan sendiri tanpa menggunakan kaidah manajemen yang berlaku (Renko & Petljak, 2018) dan bersifat sederhana (Rivai, 2017). Perubahan karakteristik suatu kawasan seperti ini sering dijumpai karena diakibatkan oleh aktivitas yang berorientasi ekonomi (Yetti, 2018).…”
Section: Pendahuluanunclassified